2006
DOI: 10.1007/s11255-006-0080-8
|View full text |Cite
|
Sign up to set email alerts
|

Survival and morbidity of HIV patients on hemodialysis and peritoneal dialysis: one center’s experience and review of the literature

Abstract: Type of renal replacement therapy does not have a significant effect on the morbidity and mortality of HIV-infected ESRD patients. Survival is worse in patients with advanced HIV disease. Both dialysis options provide similar results in HIV patients; hence, the choice of dialysis modality should be based on patient's preference and social conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 14 publications
0
6
1
Order By: Relevance
“…We found that one year survival rate of HIV positive patient was 61.4%. Our survival rate of HIV patients is lower than reported findings in the international literature that range from 74 to 95.2% in HIV positive patient receiving haemodialysis [ 10 , 17 , 18 , 31 33 ]. In the USA one year survival of HIV-positive patients receiving chronic haemodialysis was estimated at 74% [ 10 , 31 ].…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…We found that one year survival rate of HIV positive patient was 61.4%. Our survival rate of HIV patients is lower than reported findings in the international literature that range from 74 to 95.2% in HIV positive patient receiving haemodialysis [ 10 , 17 , 18 , 31 33 ]. In the USA one year survival of HIV-positive patients receiving chronic haemodialysis was estimated at 74% [ 10 , 31 ].…”
Section: Discussioncontrasting
confidence: 73%
“…In the study of Tourret et al and Trullas et al in Europe survival rate was 93.8 and 95.2% respectively [ 17 , 32 ]. Tayebey et al in Iran, found a rate of 75% [ 33 ], and Fabian et al in South Africa recently reported a 100% survival rate of HIV-positive patients [ 18 ]. In the contrary our survival rate is higher compared to the studies of Zako et al in South Africa (51%) [ 34 ] and Rodriguez et al (46%) [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies demonstrate similar outcomes between hemodialysis (HD) and peritoneal dialysis (PD) among ART-treated individuals, and modality selection depends upon patient preference and regional resources. 123, 124 Arteriovenous fistulas are the preferred vascular access, as arteriovenous grafts and catheters are associated with higher risk of infection and thrombosis. 125 There is no evidence supporting isolation of HIV-positive patients in HD units, except those with HBV co-infection.…”
Section: Ckd Progression and Eskd In The Setting Of Hiv Infectionmentioning
confidence: 99%
“…The choice of dialysis modality does not impact on survival. [16] Transplantation has been performed with success in HIV-infected patients. Preliminary short-term data in liver, kidney, and heart transplant recipients suggest that patient survival rates are similar to those in highrisk HIV-uninfected transplant recipients and there has been no increase in the prevalence of opportunistic infections.…”
Section: Eskd Due To Hiv-ckdmentioning
confidence: 99%